2014
DOI: 10.6061/clinics/2014(09)11
|View full text |Cite
|
Sign up to set email alerts
|

Open and endovascular repair of juxtarenal abdominal aortic aneurysms: a systematic review

Abstract: This systematic review focuses on the 30-day mortality associated with open surgery and fenestrated endografts for short-necked (<15 mm) juxtarenal abdominal aortic aneurysms. A search for studies published in English and indexed in the PubMed and Medline electronic databases from 2002 to 2012 was performed, using “juxtarenal abdominal aortic aneurysm” and “treatment” as the main keywords. Among the 110 potentially relevant studies that were initially identified, eight were in accordance with the inclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…5,[10][11][12] Although systematic reviews on the subject have recently been published, there is yet to be a prospective randomized trial evaluating the two operative modalities. [13][14][15][16] This study reports current data on 30-day outcomes with FEVAR and OS in AAA-Vs in a multicenter setting that we believe is most indicative of current practice patterns.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…5,[10][11][12] Although systematic reviews on the subject have recently been published, there is yet to be a prospective randomized trial evaluating the two operative modalities. [13][14][15][16] This study reports current data on 30-day outcomes with FEVAR and OS in AAA-Vs in a multicenter setting that we believe is most indicative of current practice patterns.…”
Section: Discussionmentioning
confidence: 89%
“…FEVAR is also more expensive than OS (difference due to the increased cost of the graft) and should be considered in a systems-based analysis of the two methods. 10,14 Despite its many strengths, this study has some limitations. Variables analyzed were limited to those recorded by NSQIP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endovascular procedures for the treatment of JRA include a hybrid technique, fenestrated or branched endografts, and the chimney technique 5 and are associated with more early and late postoperative complications, and especially renal insufficiency, endoleaks and thrombosis of the stent 6 . Certain authors consider endovascular approaches to be contraindicated for JRA 4 , but a recent systematic review 7 comparing open and endovascular repair of JRA showed promising results for EVAR, with significantly lower rates of two-year mortality compared with open repair (16% and 23%, respectively). However, the rates remain higher than those observed in infrarenal aneurysms with a neck length >15 mm (7.8%) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Three different systematic reviews on juxtarenal AAA found no difference in mortality between endovascular and OAR, which may be related to the strict inclusion criteria. 7,14,15 Furthermore, these reviews only included studies until 2012 or 2013. Majority of studies on FEVAR including our recent study using NSQIP is recent and is not included in these reviews.…”
Section: Discussionmentioning
confidence: 99%